Comparison of Sealer Penetration Using the EndoVac Irrigation System and Conventional Needle Root Canal Irrigation - Tuncen, Aysun Kara; ÜNAL, Bayram (My University, 2014)
Introduction: The aim of this study was to compare the effect of the EndoVac irrigation system (SybronEndo, Orange, CA) and conventional endodontic needle irrigation on sealer penetration into dentinal tubules. Methods: Forty single-rooted, recently extracted human maxillary central incisors were randomly divided into 2 groups according to the irrigation technique used: conventional endodontic needle irrigation and EndoVac irrigation. All teeth were instrumented using the ProFile rotary system (Dentsply Maillefer, Ballaigues, Switzerland) and obturated with gutta-percha and AH Plus sealer (Dentsply DeTrey, Konstanz, Germany) labeled with fluorescent dye. Transverse sections at 1, 3, and 5 mm from the root apex were examined using confocal laser scanning microscopy. The total percentage and maximum depth of sealer penetration were then measured. Results: Mann-Whitney test results showed that EndoVac irrigation resulted in a significantly higher percentage of sealer penetration than conventional irrigation at both the 1- and 3-mm levels (P < .05). However, no difference was found at the 5-mm level. The 5-mm sections in each group showed a significantly higher percentage and maximum depth of sealer penetration than did the 1- and 3-mm sections (P < .05). Conclusions: The EndoVac irrigation system significantly improved the sealer penetration at the 1- to 3-mm level over that of conventional endodontic needle irrigation.